Pengaruh Pemberian Silase Komplit Berbasis Sorgum-Clitoria Hasil Integrasi Tanaman Hortikultura Yang Berbeda Terhadap Nutrisi Tercerna Kambing Betina Lokal - Mandang, Maria; Amalo, Daud; Maranatha, Grace (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aimed to evaluate the effects of complete sorghum–Clitoria silage integrated with various horticultural crops on nutrient digestibility in local female goats. Four local female goats aged 6–8 months (body weight 17–23 kg) were used in a Latin square design (4 treatments × 4 periods). The treatments consisted of: R0 (sorghum–Clitoria silage without integration), R1 (integration with bitter melon), R2 (integration with cucumber), and R3 (integration with long bean). Measured parameters included digestible crude protein, digestible energy, and total digestible nutrient (TDN). Analysis of variance showed no significant effect (P>0.05) of the treatments on any of the observed parameters. Thus, the use of complete sorghum–Clitoria silage with different horticultural crop integrations provides comparable effectiveness in supporting nutrient digestibility in local female goats.